تفسير ابن عرفة ومواضع التقديم والتأخير فيه - جدرة, منال (University of Eloued جامعة الوادي, 2020)
" تناولت في هذه الدراسة تفسير ابن عرفة وبلاغة التقديم والتأخير فيه، مقسمة إياها إلى ثلاثة أقسام: القسم الأول ترجمت فيه للعلم ابن عرفة، وعرفت بتفسيره ومنهجه فيه، والقسم الثاني عرجت فيه على موضوع التقديم والتأخير بصفة موجزة؛ فبينت ماهية التقديم والتأخير، وكذلك أهميته، أنواعه، وأغراضه البلاغية، أما القسم الأخير فقد درست فيها ما جاء من مواضع تقديم وتأخير عند ابن عرفة؛ محاولة بذلك التوفيق بين كلام ابن عرفة والدراسات البلاغية الواردة في الموضوع. This study deals with Tafsir of Ibn Arafa the rhetoric of submission and delay in the. It is divided into three sections: The first section translated Ibn Arafa, and introduced his Tafsir and methodology. However, the second section dealt with the subject of submission and delay in a very concise. Than, I talked about the importance of submission and delay and its types as well az its rhetorical purposes. Thus, the last section has examined the points of submission and delay in Tafsir of Ibn Arafa trying to reconcile the words of Ibn Arafa with grammatical studies about this subject.
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: تفسير , ابن عرفه, موضع , التقديم والتأخير; Interpretation, Ibn Arafa, locus, introduction and delay